Decreasing spatial variability in precipitation extremes in southwestern China and the local/large‐scale influencing factors. Issue 13 (14th July 2015) - Liu, Meixian; Xu, Xianli; Sun, Alex
Abstract Climate extremes can cause devastating damage to human society and ecosystems. Recent studies have drawn many conclusions about trends in climate extremes, but few have focused on quantitative analysis of their spatial variability and underlying mechanisms. By using the techniques of overlapping moving windows, the Mann‐Kendall trend test, correlation, and stepwise regression, this study examined the spatial‐temporal variation of precipitation extremes and investigated the potential key factors influencing this variation in southwestern (SW) China, a globally important biodiversity hot spot and climate‐sensitive region. Results showed that the changing trends of precipitation extremes were not spatially uniform, but the spatial variability of these precipitation extremes decreased from 1959 to 2012. Further analysis found that atmospheric circulations rather than local factors (land cover, topographic conditions, etc.) were the main cause of such precipitation extremes. This study suggests that droughts or floods may become more homogenously widespread throughout SW China. Hence, region‐wide assessments and coordination are needed to help mitigate the economic and ecological impacts.